Physicochemical Properties of Pure Water Treated by Pure Argon Plasma Jet Generated by Microwave Discharge in Opened Atmosphere - Sergeichev, Konstantin F.; Lukina, Natalya A.; Sarimov, Ruslan M.; Smirnov, Igor G.; Simakin, Alexander V.; Dorokhov, Aleksey S.; Gudkov, Sergey V. (Frontiers in Physics, 2021)
The physicochemical properties of water activated by high-purity low-temperature argon plasma of electrodeless microwave discharge at atmospheric pressure are investigated. Such parameters of activated water as electrical conductivity, redox potential, hydrogen index (pH), the concentrations of dissolved molecular oxygen, hydrogen peroxide, OH-radicals, nitrate and nitrite anions depending on the plasma jet distance above the water surface and duration of activation were studied. Under irradiation conditions close to optimum, it was shown that the generation rate in the absence of impurities are 200 M/min for H2O2; 800 M/min for •OH and 2 mM/min for NOx. The use of plasma activated water (PAW) in agriculture has been tested. It was shown that strawberry seeds treated with a surfactant solution grow much faster than control seeds. The mechanisms of the chemical composition formation of activated water and its biological properties are discussed.